A corrosion-resistant aluminum alloy
By filling the melting nickel metal in the micropores of the micro -arc oxidation film and using medium -temperature nickel sealing holes, combined with selective laser melting technology, the problem of easy cracking or peeling of the micro -arc oxide film in the laser melting technology, significantly increased the aluminum aluminum The corrosion resistance of the alloy and the hardness of the coating.
Patent Information
- Application Number
- CN202110976727.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-08-24
AI Technical Summary
In laser melting technology, microarc oxide films are prone to cracks or peeling due to thermal stress, affecting the corrosion resistance of aluminum alloys.
By filling the micropores of the micro-arc oxidation film with molten nickel metal and using medium-temperature nickel sealing treatment, the porosity is reduced and the density is improved. Combined with selective laser melting technology, damage to the micro-arc oxidation film is avoided.
It significantly improves the density and corrosion resistance of the aluminum alloy surface microcoscopic oxide film, avoids cracks and peeling, and improves the hardness and corrosion resistance of the coating.
Smart Images

Figure CN113755918B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface treatment of aluminum alloy materials and relates to a high-performance and highly corrosion-resistant aluminum alloy material. Technical Background
[0002] Micro-arc oxidation technology is a technology with a relatively complex mechanism but a simple production process. It can prepare excellent film structures on the metal surface in situ, thereby strengthening the original performance of the metal or giving the metal new properties. It is referred to as MAO or PEO. At present, this technology mainly uses short pulses of high-intensity electrical energy in an environmentally friendly alkaline electrolyte to induce a high-density micro-arc plasma group at the contact interface between the metal substrate and the electrolyte. After a series of complex physical and chemical reactions, in-situ high-temperature sintering generates a high-performance micro-arc oxidation ceramic layer. Its working process is generally as follows: aluminum, magnesium, tin and their alloy materials are used as anode samples, which are connected and fixed and placed in a specific electrolyte solution. A steel electrolytic cell is used as the cathode material of the oxidation system. By applying a higher voltage value between the anode and the cathode, the limitation of the traditional anodic oxidation voltage is broken, so as to grow a ceramic-based protective coating in situ on the metal surface. The ceramic film formed by micro-arc oxidation is composed of a loose layer (mainly containing γ-Al2O3) and a dense layer (mainly containing α-Al2O3). From the surface of the aluminum alloy to the substrate, the cooling rate of the molten alumina gradually decreases, causing the content of γ-alumina (γ-Al2O3) to gradually decrease, while the content of α-alumina (α-Al2O3) to gradually increase. The loose layer has coarse grains, uneven surface morphology, many micropores, and poor mechanical properties; the dense layer is the main body of the micro-arc oxidation ceramic layer, with a dense structure and a very close bond with the substrate. The microhardness exceeds 2000MPa, and it has excellent wear resistance, corrosion resistance, and insulation properties. The loose layer and the dense layer are interlaced, with no obvious boundary.
[0003] Laser cladding is an important method of laser surface strengthening technology. It uses a high-energy-density laser beam to melt a very thin layer on the substrate surface and the alloy components coated on the substrate surface at the same time, forming a rapid solidification process of an alloy layer on the substrate surface with completely different components and properties from the substrate. According to the different alloy supply methods, laser cladding can be divided into a pre-setting method and a synchronous supply method. The alloy pre-setting method refers to a method in which the alloy material to be clad is pre-covered on the substrate surface in a certain way, and then a laser beam is used to scan the surface of the alloy pre-cladding layer. The synchronous supply method refers to a method in which a special feeding system is used to directly feed the alloy material into the laser action area during the laser cladding process. The alloy material selected can also be powder, wire and plate.
[0004] In the prior art, aluminum materials are usually subjected to micro-arc oxidation, and then the porous layer obtained by micro-arc oxidation is melted again by laser melting to obtain a smooth surface. For example, CN201110297310 discloses a ceramic film layer on a metal surface and a preparation method thereof. The surface of light alloys such as aluminum alloys can be ceramicized, and the ceramic can be thickened by laser cladding. And this relatively thick ceramic layer can be used in many fields. In addition, the laser cladding process cannot be promoted on a large scale precisely because it cannot form a good combination with metals, and laser cladding on micro-arc oxidation ceramics can combine these two points very well. That is, the metal and the micro-arc oxidation ceramic layer are connected at the atomic level, and the micro-arc oxidation ceramic and the laser cladding ceramic can achieve atomic-level connection, so that the metal and the ceramic layer are integrated, overcoming the defects of the micro-arc oxidation process and the laser cladding process. As described in Example 1: Example 1 takes the mechanical sealing ring with aluminum alloy as the base as an example. Here, aluminum alloy 2219 is forged and formed. After mechanical processing, shaping, grinding, and heat treatment, the sealing ring blank can be made; and after degreasing, cleaning, micro-arc oxidation, cleaning, grinding and other subsequent treatments, it can be completed. The micro-arc oxidation electrolyte is mainly composed of water glass, and the pH value is adjusted between 11-13. The solution flows in the electrolytic cell through a circulating cooling system. The stainless steel electrolytic cell is connected to the cathode of the power supply, and the aluminum alloy sealing ring blank is connected to the anode of the power supply. The electrolyte temperature is 20-50°C by stirring and cooling with an air pump, and the treatment time is 30-50 minutes. A dense alumina ceramic layer is grown in situ on the surface of the sealing ring. After testing, the thickness is about 60 microns, and its surface hardness reaches HV1100. After treatment, the sample with the film layer is rinsed with water and dried, and then directly subjected to laser cladding treatment. Laser remelting uses SLCF.X12x25 C02 laser processing machine, and argon protection is used during remelting. In order to keep a certain nanostructure of the ceramic coating after remelting and reduce defects such as cracks in the remelted layer, relatively low laser power and energy density are used for remelting. The laser remelting process parameters used are: laser power is 900W, rectangular spot size is 5mm×3mm, laser scanning direction is along the 3mm side of the spot, scanning speed is 700mm / min, and overlap is 20%. The composition of the ceramic material is Al2O3-13%TiO2, the agglomerate size distribution range is 10--50 microns, and its original nanoparticles are 30--80 nanometers.
[0005] However, those skilled in the art know that during laser melting, cracks and pores are likely to appear in the cladding layer. The laser power used in this field is 900W, and its temperature is extremely high. It will melt the powder and the micro-arc oxide film together. However, at such a high temperature, the micro-arc oxide film, which originally has effective bonding with aluminum, is very likely to crack due to the thermal stress generated by laser melting, and even the substrate and the oxide film will peel off. Summary of the invention
[0006] Based on the technical problem in the prior art that cracks may appear in the micro-arc oxidation film or the ceramic film may peel off when the micro-arc oxidation film is treated by laser melting technology, the present invention provides a corrosion-resistant aluminum alloy, wherein the surface of the aluminum alloy is treated by micro-arc oxidation to obtain a micro-arc oxidation film, the micropores on the surface of the oxygen micro-arc oxidation film have a pore size of 1-5 μm, a thickness of 8-15 μm, and a porosity of 10-17.5%, molten nickel metal solids are arranged in the micropores, and then medium-temperature nickel is used to seal the pores to obtain a micro-arc oxidation aluminum alloy with a porosity of 2-3%, wherein the molten nickel metal solids are obtained by laser melting, and the laser melting parameters are as follows:
[0007] Laser output power 100-125W; spot diameter 2-3mm; laser beam scanning rate 5-10mm / s, large area scanning laser overlap rate 30%-60%, inert argon protective gas.
[0008] Furthermore, after the aluminum alloy is sealed, it is polished, the main component of the polishing liquid used in the polishing is α-Al2O3, and the surface roughness after polishing is Ra<0.2μm.
[0009] Furthermore, the aluminum alloy is subjected to surface pretreatment before micro-arc oxidation:
[0010] (1) Mechanical grinding: The aluminum alloy samples were polished with 800# and 1200# sandpaper respectively;
[0011] (2) Degreasing: 12-15wt.% sulfuric acid, 1.5-2.5wt.% surfactant, room temperature, time is 5-7min; water washing: distilled water, 15-20s;
[0012] (3) Acid pickling: nitric acid 15-25wt.%; sulfuric acid 10-15wt.%; room temperature; time: 4-6min; water washing: distilled water, 15-20s.
[0013] Furthermore, the electrolyte used in the micro-arc oxidation includes Na2SiO3 5-15 g / L, NaOH 1-2 g / L, Na2WO4 1-5 g / L and glycerol 4-6 ml / L.
[0014] Furthermore, the electrolysis parameters of the micro-arc oxidation are: forward voltage 300~500V, negative voltage 100~200V, positive duty cycle 15~25%, negative duty cycle 5~10%, pulse frequency 300~400Hz, and oxidation time 20~40min.
[0015] Furthermore, the precursor of the molten nickel metal solid is a 15-20wt.% nano nickel dispersion, and the nanometer scale is 50-100nm.
[0016] Furthermore, the precursor enters the pores of the micro-arc oxidation film by spin coating, and the spin coating parameters are: rotation speed of 2000-2500 rpm, spin coating time of 30-40s, spin coating times of 5-9 times, and vacuum spin coater.
[0017] Furthermore, the sealing liquid of the medium-temperature nickel sealing is composed of: 5-10 g / L nickel acetate, 5-7 g / L boric acid, 0.3-0.5 g / L aminotrimethylene phosphoric acid, 0.1-0.2 g / LEDTA-2Na, 0.03-0.05 g / L octylphenol polyoxyethylene ether and deionized water.
[0018] Furthermore, the sealing parameters are: pH=5.7±0.3, temperature 85-90°C, and time 15-20min.
[0019] The corrosion-resistant aluminum alloy is prepared by the following method:
[0020] (1) Surface pretreatment;
[0021] (2) Micro-arc oxidation to obtain a micro-arc oxidation film ceramic layer;
[0022] (3) multiple coatings of nickel nanodispersions;
[0023] (4) Selective laser melting processing;
[0024] (5) Inorganic sealing;
[0025] (6) Polishing treatment.
[0026] Before the workpiece of the present invention is subjected to surface treatment, the oil stains on the surface must be removed first to ensure the bonding strength between the micro-arc oxidation film and the base metal, to ensure the smooth progress of the chemical reaction of the conversion film, and to obtain a conversion film layer of qualified quality. Aluminum alloy is an amphoteric metal that can react with both acid and alkali, so the aluminum alloy can be degreased by either alkaline degreasing or acidic degreasing. Since the dissolution rate of aluminum alloy in acid is much lower than that in alkali, the surface of the workpiece is not easy to darken after degreasing. The present invention uses an acidic degreasing method to degrease the aluminum alloy. Acidic degreasing can not only remove dirt on the surface of the aluminum alloy, but also remove oxides on its surface, and hydrogen embrittlement will not occur.
[0027] Aluminum alloy workpieces cannot be subjected to micro-arc oxidation treatment after the degreasing process. Generally, there are defects such as natural oxide film and processing stripes on the surface. Corrosion treatment is required to remove the natural oxide film and activate the surface so that the bright metal matrix is exposed on the surface of the aluminum alloy, providing a good matrix surface for the next step of surface treatment.
[0028] Water washing: Any aluminum workpiece treated with chemical solution should be washed with water immediately after being removed from the treatment solution, and the sooner the better. Because the workpiece is exposed to the air after leaving the treatment solution, the surface is in an uneven state, and the chemical agent needs to be washed away with water immediately to terminate the chemical reaction and prevent the chemical agent from being brought into the next treatment solution and contaminating the next chemical treatment tank. Generally, the workpiece is not allowed to enter the chemical treatment tank in a dry state. It needs to be washed with water to wet the surface of the workpiece before entering the chemical treatment tank for treatment to prevent uneven local reaction.
[0029] Micro-arc oxidation is performed in alkaline electrolytes. Currently, alkaline electrolytes are divided into four major systems: silicate electrolytes, sodium hydroxide electrolytes, phosphate electrolytes and aluminate electrolytes. In actual application, the selected electrolyte composition must be matched with the modified aluminum alloy material. The present invention adopts the widely used silicate electrolyte. Na2SiO3 is a film-forming substance. As the content of the film-forming substance continues to increase, the thickness of the film layer increases rapidly, and the thickness of the dense layer in the corresponding film layer also continues to increase. The dense layer is the main layer to improve the comprehensive performance of the film layer. Therefore, the thickness of the dense layer is increased, and the corrosion resistance of the film layer is improved accordingly.
[0030] NaOH is the pH adjuster of the solution, which ensures that the pH value of the solution is between 10 and 12, and provides a stable electrolyte environment for the preparation of micro-arc oxidation film.
[0031] The sodium tungstate additive will have an effect on the dense layer of the film without affecting the phase structure of the film. When the content of sodium tungstate gradually increases, the thickness of the film increases. This is because the sodium tungstate additive promotes the growth of the dense layer, so the corrosion resistance of the film is also significantly improved.
[0032] As an additive, propylene glycol can reduce the micropores on the surface of the ceramic membrane and improve the surface smoothness, thereby making the ceramic membrane more uniform and dense and greatly enhancing the corrosion resistance.
[0033] Power supply mode: The initial micro-arc oxidation process uses a DC constant current power supply, but it is difficult to control the discharge characteristics of the metal surface, so it is less used now. The pulse voltage generated by the pulse AC power supply has a "needle tip" effect, which greatly reduces the local area and overlaps the surface micropores to form a film layer with small roughness and uniform thickness.
[0034] Pulse frequency: Under high pulse frequency, the mass fraction of the dense layer increases, the surface roughness decreases, the hardness of the film layer increases, the wear resistance is enhanced, and the obtained ceramic layer has excellent performance.
[0035] Duty cycle: Pulse duty cycle is an important factor affecting the characteristics of ceramic membranes. Pulse width determines the duration and density of spark discharge. Increasing pulse width is conducive to increasing the mass fraction of α-Al2O3 and improving the hardness of ceramic membranes. However, excessive pulse width will make the discharge more intense, thereby increasing the surface roughness of the ceramic membrane. Figure 1 (Left) and its method diagram, obvious volcanic micropores are visible.
[0036] Nickel nano dispersion: Nickel nanoparticles were prepared by the nano nickel preparation method disclosed in Example 1 of CN101053906A, and the preparation method was as follows: 18 g nickel chloride, 18 g PVP, 150 g ethanol and 150 g toluene were added to 300 g distilled water, and the aqueous mixture was stirred at 40° C. to prepare a reverse microemulsion. 40 g hydrazine hydrate was added to the reverse microemulsion aqueous solution, which was stirred for 30 minutes to form a nickel-hydrazine complex. 0.04 mole of NaBH4 was added to the reverse microemulsion containing the nickel-hydrazine complex, which was stirred for 1 hour to prepare nickel particles by reduction. The nickel nanoparticles were separated from the reverse microemulsion by centrifugation. After washing the separated nanoparticles 3 times with acetone and distilled water, the nickel nanoparticles were obtained by drying at 50° C. for 3 hours in a vacuum drying oven. However, through experimental characterization, the size of the nickel nanoparticles prepared by the present invention is about 50-100nm, which is not reasonable to obtain the 10-50nm nano nickel obtained in CN101053906A. The obtained 50-100nm is prepared into a 15-20wt.% dispersion, and the dispersion is dripped onto the surface of the aluminum alloy after micro-arc oxidation through a dropper. A vacuum spin coater is used with a rotation speed of 2000-2500rpm, a spin coating time of 30-40s, and a spin coating number of 5-9 times, and then at 40-50 o C vacuum drying for 3-5h.
[0037] Since the micro-arc surface is composed of a porous layer, an intermediate layer, and a dense layer from top to bottom, the porous layer is a volcano-shaped micropore. During the spin coating process, nickel nanoparticles enter the micropores of the micro-arc oxidation film to fill them, and then the nickel nanoparticles are selectively dissolved by subsequent laser melting.
[0038] Selective laser melting treatment; the selectivity means that nickel is selectively melted by high-energy laser energy, while micro-arc oxidation does not melt, thereby achieving effective sealing of nickel. It is well known in the art that the melting temperature of micro-arc oxidation film aluminum oxide is about 2055, the melting point of pure nickel particles is about 1435°C, and the temperature of Ni60 alloy is about 1027 o C, the melting temperature of the nickel nanoparticles prepared by the present invention is about 500-600 oC. If selective laser melting is to be achieved, only nickel is remelted without melting the micro-arc oxide film, the output power of the laser melting needs to be controlled. According to the test of the present invention, when the laser output power is 75-125W, the local surface temperature is 700-800 o C, when the power is 125W, the local surface temperature is 1200-1500℃. In addition, considering that when the laser irradiates the surface of the film, the heat will dissipate into the air and the inside of the film, resulting in the temperature not reaching the melting point of nickel, the output power of the laser is selected to be 100-125W. Under the output power, only the nickel nanoparticles are dissolved, and the alumina micro-arc oxidation ceramic layer has no effect at all.
[0039] At this time, nickel nanoparticles are filled in the micron pores of the micro-arc oxidation film. Through laser melting, the nickel nanoparticles are coated in the micropores of the micro-arc oxidation film in a molten state. However, after the melt is cooled, there must be a small gap between the nickel melt and the micro-arc oxidation film. The existence of the gap will significantly affect the corrosion resistance of the micro-arc oxidation film. Therefore, it is necessary to fill the gap between the melt and the pores.
[0040] In addition, since the thickness of the micro-arc oxidation is 8-15μm, the local laser melting nano-nickel seal will not have a significant thermal impact on the aluminum material, that is, it will not generate thermal stress on the substrate, so cracks and peeling will not occur.
[0041] The filling method used is the inorganic sealing method, using the common nickel sealing agent on the market: 5-10g / L nickel acetate, 5-7g / L boric acid, 0.3-0.5g / L aminotrimethylene phosphoric acid, 0.1-0.2g / LEDTA-2Na, 0.03-0.05g / L octylphenol polyoxyethylene ether, pH=5.7±0.3, temperature 85-90℃, time 15-20min. The main principle used in the sealing process is that after nickel ions enter the gap, a hydrolysis reaction occurs to generate nickel hydroxide precipitation, which fills the pores to achieve the purpose of sealing the pores. The reaction formula is
[0042] Ni(CHCOO)2+2H2O→Ni(OH)2+2CH3COOH.
[0043] In addition, aminotrimethylene phosphoric acid, EDTA-2Na and octylphenol polyoxyethylene ether are indispensable additives for improving the sealing effect. It should be noted that an obvious "powder bloom" phenomenon will appear during the sealing process. Although additives such as aminotrimethylene phosphoric acid can improve the "powder bloom" phenomenon to a certain extent, most of the micro-arc oxidation channels are sealed by the use of nickel melt, and the gap between the melt and the channel is small, so the "powder bloom" phenomenon is inevitable, so the "powder bloom" needs to be removed.
[0044] Due to the presence of powder frost and the roughness and unevenness of the micro-arc oxidation film itself, the crater protrusions and powder frost of the micro-arc oxidation film need to be processed. They can be effectively removed by polishing. The surface removal amount is 1-3μm, and the obtained surface roughness is <0.2μm.
[0045] As attached Figure 1 (right), attached Figure 2 , Attachment Figure 3 , Attachment Figure 4 As shown, there is an obvious nickel molten part near the volcanic micropores, and in the enlarged image, it can be seen that there is a nickel sealing layer introduced by the nickel sealing agent between the nickel molten part and the micro-arc oxidation pores.
[0046] Beneficial technical effects
[0047] 1. The present invention controls the power of the laser and selectively melts the nickel nanoparticles by the selective laser melting technology without affecting the aluminum oxide micro-arc oxidation layer, thereby effectively avoiding the cracking problem caused by the thermal expansion and deformation of the aluminum alloy matrix.
[0048] 2. The present invention effectively reduces the heat intensity of the laser by selecting a nickel nano-dispersion liquid with a lower melting point.
[0049] 3. The present invention introduces nickel sealing between the molten nickel portion and the micro-arc oxidation pores, thereby effectively reducing the porosity of the micro-arc oxidation film surface, increasing the surface density, and thus improving the corrosion resistance of the aluminum alloy.
[0050] Instruction Manual
[0051] Attached Figure 1 : SEM images of the surface of the micro-arc oxidation film of the present invention (left) and the micro-arc oxidation film after sealing (right).
[0052] Attached Figure 2 : SEM image of the aluminum alloy obtained in Example 2 of the present invention.
[0053] Attached Figure 3 : SEM image of the aluminum alloy obtained in Example 3 of the present invention.
[0054] Attached Figure 4 : SEM partial enlarged image of the aluminum alloy obtained in Example 2 of the present invention. DETAILED DESCRIPTION
[0055] Example 1
[0056] A corrosion-resistant aluminum alloy is prepared by the following method:
[0057] (1) Surface pretreatment:
[0058] (a) Mechanical grinding: The aluminum alloy samples were polished with 800# and 1200# sandpaper respectively;
[0059] (b) Degreasing: 12wt.% sulfuric acid, 1.5wt.% surfactant, room temperature, time 5min; washing: distilled water, 15s;
[0060] (c) Acid pickling: nitric acid 15wt.%; sulfuric acid 10wt.%; room temperature; time: 4min; water washing: distilled water, 15s.
[0061] (2) Micro-arc oxidation to obtain a micro-arc oxidation film ceramic layer: Na2SiO3 5g / L, NaOH 1g / L, Na2WO4 1g / L; propylene glycol 4ml / L; forward voltage 300V, negative voltage 100V, positive duty cycle 15%, negative duty cycle 5%, pulse frequency 300Hz, oxidation time 200min.
[0062] (3) Multiple coatings of nickel nano-dispersion: The size of nickel in the nickel nano-dispersion is 50-100 nm and the content is 15 wt.%.
[0063] The multiple coatings were performed using a vacuum spin coater at a rotation speed of 2000 rpm, a spin coating time of 30 s, 5 spin coatings, and then at 40 o C and dried in vacuum for 3 h.
[0064] (4) Selective laser melting process: In the selective laser melting process, the laser output power is 100 W; the spot diameter is 2 mm; the laser beam scanning rate is 5 mm / s, the large area scanning laser overlap rate is 30%, and the inert argon protective gas is used.
[0065] (5) Inorganic sealing: Inorganic sealing uses medium-temperature nickel sealing. The sealing liquid composition is as follows: 5g / L nickel acetate, 5g / L boric acid, 0.3g / L aminotrimethylene phosphoric acid, 0.1g / LEDTA-2Na, 0.03g / L octylphenol polyoxyethylene ether, pH=5.7, temperature 85℃, time 15min.
[0066] After sealing, wash with deionized water and dry at 30°C.
[0067] (6) Polishing treatment: the main component of the polishing liquid used for polishing is α-Al2O3, and the surface roughness after polishing is Ra<0.2μm.
[0068] Example 2
[0069] A corrosion-resistant aluminum alloy is prepared by the following method:
[0070] (1) Surface pretreatment:
[0071] (a) Mechanical grinding: The aluminum alloy samples were polished with 800# and 1200# sandpaper respectively;
[0072] (b) Degreasing: 14wt.% sulfuric acid, 2wt.% surfactant, room temperature, time 6min; washing: distilled water, 17.5s;
[0073] (c) Acid pickling: nitric acid 20wt.%; sulfuric acid 12.5wt.%; room temperature; time: 5min; water washing: distilled water, 17.5s.
[0074] (2) Micro-arc oxidation to obtain a micro-arc oxidation film ceramic layer: Na2SiO3 20g / L, NaOH 1.5g / L, Na2WO4 3g / L; propylene glycol 5ml / L; forward voltage 400V, negative voltage 150V, positive duty cycle 20%, negative duty cycle 7.5%, pulse frequency 350Hz, oxidation time 30min.
[0075] (3) Multiple coatings of nickel nano-dispersion: The size of nickel in the nickel nano-dispersion is 50-100 nm and the content is 17.5 wt.%.
[0076] The multiple coatings were performed using a vacuum spin coater at a rotation speed of 2300 rpm, a spin coating time of 35 s, 8 spin coatings, and then at 45 o C vacuum drying for 4 h.
[0077] (4) Selective laser melting process: In the selective laser melting process, the laser output power is 120 W; the spot diameter is 2.5 mm; the laser beam scanning rate is 7.5 mm / s, the large area scanning laser overlap rate is 45%, and the inert argon protective gas is used.
[0078] (5) Inorganic sealing: Inorganic sealing uses medium-temperature nickel sealing, and the sealing liquid composition is as follows: 7.5g / L nickel acetate, 6g / L boric acid, 0.4g / L aminotrimethylene phosphoric acid, 0.15g / LEDTA-2Na, 0.04g / L octylphenol polyoxyethylene ether, pH=5.7, temperature 87.5℃, time 17.5min.
[0079] After sealing, wash with deionized water and dry at 35°C.
[0080] (6) Polishing treatment: the main component of the polishing liquid used for polishing is α-Al2O3, and the surface roughness after polishing is Ra<0.2μm.
[0081] Example 3
[0082] A corrosion-resistant aluminum alloy is prepared by the following method:
[0083] (1) Surface pretreatment:
[0084] (a) Mechanical grinding: The aluminum alloy samples were polished with 800# and 1200# sandpaper respectively;
[0085] (b) Degreasing: 15wt.% sulfuric acid, 2.5wt.% surfactant, room temperature, time 7min; washing: distilled water, 20s;
[0086] (c) Acid pickling: nitric acid 25wt.%; sulfuric acid 15wt.%; room temperature; time: 6min; water washing: distilled water, 20s.
[0087] (2) Micro-arc oxidation to obtain a micro-arc oxidation film ceramic layer: Na2SiO3 15g / L, NaOH 2g / L, Na2WO4 5g / L; propylene glycol 6ml / L; forward voltage 500V, negative voltage 200V, positive duty cycle 15~25%, negative duty cycle 10%, pulse frequency 400Hz, oxidation time 40min.
[0088] (3) Multiple coatings of nickel nano-dispersion: The size of nickel in the nickel nano-dispersion is 50-100 nm and the content is 20 wt.%.
[0089] The multiple coatings were performed using a vacuum spin coater at a rotation speed of 2500 rpm, a spin coating time of 40 s, 9 spin coating times, and then at 50 o C and dried in vacuum for 5 h.
[0090] (4) Selective laser melting process: In the selective laser melting process, the laser output power is 125 W; the spot diameter is 3 mm; the laser beam scanning rate is 10 mm / s, the large area scanning laser overlap rate is 60%, and the inert argon protective gas is used.
[0091] (5) Inorganic sealing: Inorganic sealing uses medium-temperature nickel sealing, and the sealing liquid composition is as follows: 10g / L nickel acetate, 7g / L boric acid, 0.5g / L aminotrimethylene phosphoric acid, 0.2g / LEDTA-2Na0.03-0.05g / L octylphenol polyoxyethylene ether, pH=5.7, temperature 90℃, time 20min.
[0092] After sealing, wash with deionized water and dry at 40℃.
[0093] (6) Polishing treatment: the main component of the polishing liquid used for polishing is α-Al2O3, and the surface roughness after polishing is Ra<0.2μm.
[0094] Comparative Example 1
[0095] An aluminum alloy material is prepared by the following method:
[0096] (1) Surface pretreatment:
[0097] (a) Mechanical grinding: The aluminum alloy samples were polished with 800# and 1200# sandpaper respectively;
[0098] (b) Degreasing: 14wt.% sulfuric acid, 2wt.% surfactant, room temperature, time 6min; washing: distilled water, 17.5s;
[0099] (c) Acid pickling: nitric acid 20wt.%; sulfuric acid 12.5wt.%; room temperature; time: 5min; water washing: distilled water, 17.5s.
[0100] (2) Micro-arc oxidation to obtain a micro-arc oxidation film ceramic layer: Na2SiO3 20g / L, NaOH 1.5g / L, Na2WO4 3g / L; propylene glycol 5ml / L; forward voltage 400V, negative voltage 150V, positive duty cycle 20%, negative duty cycle 7.5%, pulse frequency 350Hz, oxidation time 30min.
[0101] (3) Inorganic sealing: Inorganic sealing uses medium-temperature nickel sealing, and the sealing liquid composition is as follows: 7.5g / L nickel acetate, 6g / L boric acid, 0.4g / L aminotrimethylene phosphoric acid, 0.15g / LEDTA-2Na, 0.04g / L octylphenol polyoxyethylene ether, pH=5.7, temperature 87.5℃, time 17.5min.
[0102] After sealing, wash with deionized water and dry at 35°C.
[0103] (4) Polishing treatment: the main component of the polishing liquid used for polishing is α-Al2O3, and the surface roughness after polishing is Ra<0.2μm.
[0104] Comparative Example 2
[0105] An aluminum alloy material is prepared by the following method:
[0106] (1) Surface pretreatment:
[0107] (a) Mechanical grinding: The aluminum alloy samples were polished with 800# and 1200# sandpaper respectively;
[0108] (b) Degreasing: 14wt.% sulfuric acid, 2wt.% surfactant, room temperature, time 6min; washing: distilled water, 17.5s;
[0109] (c) Acid pickling: nitric acid 20wt.%; sulfuric acid 12.5wt.%; room temperature; time: 5min; water washing: distilled water, 17.5s.
[0110] (2) Micro-arc oxidation to obtain a micro-arc oxidation film ceramic layer: Na2SiO3 20g / L, NaOH 1.5g / L, Na2WO4 3g / L; propylene glycol 5ml / L; forward voltage 400V, negative voltage 150V, positive duty cycle 20%, negative duty cycle 7.5%, pulse frequency 350Hz, oxidation time 30min.
[0111] (3) Multiple coatings of nickel nano-dispersion: The size of nickel in the nickel nano-dispersion is 50-100 nm and the content is 17.5 wt.%.
[0112] The multiple coatings were performed using a vacuum spin coater at a rotation speed of 2300 rpm, a spin coating time of 35 s, 8 spin coatings, and then at 45 o C vacuum drying for 4 h.
[0113] (4) Inorganic sealing: Inorganic sealing uses medium-temperature nickel sealing, and the sealing liquid composition is as follows: 7.5g / L nickel acetate, 6g / L boric acid, 0.4g / L aminotrimethylene phosphoric acid, 0.15g / LEDTA-2Na, 0.04g / L octylphenol polyoxyethylene ether, pH=5.7, temperature 87.5℃, time 17.5min.
[0114] After sealing, wash with deionized water and dry at 35°C.
[0115] (5) Polishing treatment: the main component of the polishing liquid used for polishing is α-Al2O3, and the surface roughness after polishing is Ra<0.2μm.
[0116]
[0117] As shown in the table above, by filling the pores of the micro-arc oxidation film with nickel metal having a low melting point, and then selectively melting the nickel metal through laser melting technology, and then using nickel sealing agent treatment, the density of the micro-arc oxidation film on the surface of the aluminum alloy can be effectively improved, thereby significantly improving its corrosion resistance. The corrosion current density is 2.6235*10 -8 , and the hardness of the coating is increased to 1862HV. In addition, if only nano-nickel filling is performed without laser melting treatment, the pores cannot be effectively sealed, that is, the corrosion resistance and hardness of the aluminum alloy in Example 1-2 do not change significantly.
[0118] The above embodiments are only for illustrating the technical idea of the present invention, and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the present invention; any technology not involved in the present invention can be realized by existing technologies.
Claims
1. A corrosion-resistant aluminum alloy, characterized in that The aluminum alloy surface is subjected to micro-arc oxidation treatment to obtain a micro-arc oxidation film, the micropores on the surface of the micro-arc oxidation film have a pore size of 1-5 μm, a thickness of 8-15 μm, and a porosity of 10-17.5%, molten nickel metal solids are arranged in the micropores, and then medium-temperature nickel is used to seal the pores to obtain a micro-arc oxidation aluminum alloy with a porosity of 2-3%, wherein the molten nickel metal solids are obtained by laser melting, and the laser melting parameters are as follows: Laser output power 100-125W; spot diameter 2-3mm; laser beam scanning rate 5-10mm / s, large area scanning laser overlap rate 30%-60%, inert argon protective gas; The precursor of the molten nickel metal solid is a 15-20wt.% nano nickel dispersion with a nanometer scale of 50-100nm; The precursor enters the pores of the micro-arc oxidation film by spin coating, and the spin coating parameters are: rotation speed of 2000-2500rpm, spin coating time of 30-40s, spin coating times of 5-9 times, and spin coating using a vacuum spin coater.
2. A corrosion-resistant aluminum alloy as claimed in claim 1, characterized in that After the aluminum alloy is sealed, it is polished. The main component of the polishing liquid used in the polishing is α-Al2O3. The surface roughness Ra after polishing is less than 0.2 μm.
3. A corrosion-resistant aluminum alloy as claimed in claim 1, characterized in that The aluminum alloy is subjected to surface pretreatment before micro-arc oxidation: (1) Mechanical grinding: The aluminum alloy samples were polished with 800# and 1200# sandpaper respectively; (2) Degreasing: 12-15wt.% sulfuric acid, 1.5-2.5wt.% surfactant, room temperature, time 5-7min; water washing: distilled water, 15-20s; (3) Pickling: nitric acid 15-25wt.%, sulfuric acid 10-15wt.%; room temperature; Time: 4-6 minutes; Wash: distilled water, 15-20s.
4. A corrosion-resistant aluminum alloy as claimed in claim 1, characterized in that The electrolyte used in the micro-arc oxidation includes Na2SiO3 5-15g / L, NaOH 1-2g / L, Na2WO4 1-5g / L and glycerol 4-6ml / L.
5. A corrosion-resistant aluminum alloy as claimed in claim 4, characterized in that The electrolysis parameters of the micro-arc oxidation are: forward voltage 300-500V, negative voltage 100-200V, positive duty cycle 15-25%, negative duty cycle 5-10%, pulse frequency 300-400Hz, and oxidation time 20-40min.
6. A corrosion-resistant aluminum alloy as claimed in claim 1, characterized in that The sealing liquid for medium-temperature nickel sealing is composed of: 5-10 g / L nickel acetate, 5-7 g / L boric acid, 0.3-0.5 g / L aminotrimethylene phosphoric acid, 0.1-0.2 g / L EDTA-2Na, 0.03-0.05 g / L octylphenol polyoxyethylene ether and deionized water.
7. A corrosion-resistant aluminum alloy as claimed in claim 6, characterized in that The sealing parameters are as follows: pH=5.7±0.3, temperature 85-90° C., and time 15-20 min.
Citation Information
Patent Citations
Method for manufacturing nickel nanoparticles
CN101053906A
Ceramic membrane layer on metal surface and preparation method thereof
CN103014706A
SiO2 micro-arc oxidation coating and preparation method thereof
CN109161890A
Coating treatment method
CN109355655A